2014
DOI: 10.4049/jimmunol.1401104
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Ccr7 Expression in Distinct Lineages of Lung Dendritic Cells

Abstract: Adaptive immune responses to inhaled allergens are induced following CCR7-dependent migration of pre-DC (precursor of DC)-derived conventional dendritic cells (cDCs) from the lung to regional lymph nodes (LN). However, monocyte-derived (mo) DCs in the lung express very low levels of Ccr7, and consequently do not migrate efficiently to LN. To investigate the molecular mechanisms that underlie this dichotomy, we studied epigenetic modifications at the Ccr7 locus of murine cDCs and moDCs. When expanded from bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…It was recently reported that histone 3 lysine 27 trimethylation (H3K27me3) modulates CCR7 expression in DCs 36 . To investigate if miR-155 regulates CCR7 expression in DCs by affecting H3K27me3, a chromatin immunoprecipitation (ChIP) assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that histone 3 lysine 27 trimethylation (H3K27me3) modulates CCR7 expression in DCs 36 . To investigate if miR-155 regulates CCR7 expression in DCs by affecting H3K27me3, a chromatin immunoprecipitation (ChIP) assay was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Our in‐vitro experiments were performed with isolated lamina propria DC as well as with GM‐CSF matured BMDC. It is important to realize that expression of CCR7 on BMDC is lower in GM‐CSF‐derived cultures compared to FLT3L‐matured BMDC . This might imply that the differences observed could be even more pronounced when using alternative methods of cell preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Murine lung and LN cells were isolated and analysed by flow cytometry as previously described . Briefly, harvested lungs and mLNs were manually cut with scissors and digested with Liberase TM (100 μg/mL; Roche Diagnostics), collagenase XI (250 μg/mL), hyaluronidase 1a (1 mg/mL), and DNase I (200 μg/mL; Sigma, St. Louis, MO) for 1 hour (lungs) or 30 minutes (mLNs) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…All antibodies were purchased from BioLegend or BD Biosciences. In some experiments, peanut uptake by lung cDCs was evaluated following instillation of peanut labelled with Alexa Fluor 647 (Invitrogen) as described previously …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation